3D Continuously Porous Graphene for Energy Applications. Issue 15 (25th February 2022) - Han, Jiuhui; Johnson, Isaac; Chen, Mingwei
Abstract: Constructing bulk graphene materials with well‐reserved 2D properties is essential for device and engineering applications of atomically thick graphene. In this article, the recent progress in the fabrications and applications of sterically continuous porous graphene with designable microstructures, chemistries, and properties for energy storage and conversion are reviewed. Both template‐based and template‐free methods have been developed to synthesize the 3D continuously porous graphene, which typically has the microstructure reminiscent of pseudo‐periodic minimal surfaces. The 3D graphene can well preserve the properties of 2D graphene of being highly conductive, surface abundant, and mechanically robust, together with unique 2D electronic behaviors. Additionally, the bicontinuous porosity and large curvature offer new functionalities, such as rapid mass transport, ample open space, mechanical flexibility, and tunable electric/thermal conductivity. Particularly, the 3D curvature provides a new degree of freedom for tailoring the catalysis and transport properties of graphene. The 3D graphene with those extraordinary properties has shown great promises for a wide range of applications, especially for energy conversion and storage. This article overviews the recent advances made in addressing the challenges of developing 3D continuously porous graphene, the benefits and opportunities of the new materials for energy‐related applications, and the remaining challenges that warrant future study. Abstract : 3D continuously porous graphene formed by folding a single‐sheet graphene into a 3D porous architecture has well‐retained 2D properties of graphene and novel functionalities from 3D structure, representing a distinct class of graphene materials with numerous unique and extraordinary properties. A comprehensive review of 3D continuously porous graphene and their applications in energy conversion and storage is provided.